Effect of Servant Leadership and Leader-Member Exchange on Organizational Commitment through Job Satisfaction - Hadi, Marhendri Indria; Riva'i, Alimuddin Rizal (Management Analysis Journal, 2022)
This study aims to analyze the effect of servant leadership and leader-member exchange on organizational commitment with job satisfaction as a mediation. The population in this study were employees of the Central Java I Regional Tax Office who had no subordinates totaling 135 respondents. Sampling was done by using census sampling technique that took all the existing population. The type of data used is primary data and the method of data collection is done by using a questionnaire. The analysis used in this study is linear regression analysis using SPSS 21 software. The results of the study show that servant leadership and leader-member exchange have a positive and significant effect on job satisfaction. In addition, servant leadership, leader-member exchange, and job satisfaction have a positive and significant impact on organizational commitment. Job satisfaction also mediates the effect of servant leadership and leader-member exchange on organizational commitment.